Crowdsourcing and community engagement: a qualitative analysis of the 2BeatHIV contest - Allison Mathews; Samantha Farley; Lisa Hightow-Weidman; Kate Muessig; Stuart Rennie; Joseph D. Tucker (Elsevier, 2018)
Background: As HIV cure research advances, it is important to engage local communities. Crowdsourcing may be an effective, bottom-up approach. Crowdsourcing contests elicit public contributions to solve problems and celebrate finalists. We examine the development of a crowdsourcing contest to understand public perspectives about HIV cure research.Methods: We used flyers, emails, online advertisement and phone calls to recruit a convenience sample of community members to participate in focus-group discussions. Participants developed a contest name, logo and hashtag. Qualitative analysis identified emergent themes in the focus group transcripts.Results: Seventy-one people participated in four focus groups. Emergent themes for HIV cure engagement included: (1) emphasising collective approaches to HIV cure; (2) dispelling myths to spur discussion; (3) using HIV cure as motivation for participation; and (4) using creative community engagement.Conclusion: Crowdsourcing contests may be useful for engaging local communities, developing culturally tailored awareness campaign messaging, and encouraging the public to learn more about HIV cure research.